Investigating the role of student engagement in the relationship between ICT accessibility and educational quality in Cambodian universities - Phon, Samean; Ali, Dhakir Abbas (Edelweiss Applied Science and Technology, 2025)
This study investigates the mediating role of student engagement in the relationship between Information and Communication Technology (ICT) accessibility and educational quality in Cambodian universities. Grounded in established educational theories, the research employed a quantitative method using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0. Data were collected via 346 distributed questionnaires, of which 306 valid responses were analyzed from five public universities. The measurement model demonstrated excellent reliability and validity, with Cronbach’s alpha and composite reliability values exceeding 0.719 to 0.905, and average variance extracted (AVE) values above 0.640. Structural model results revealed that ICT accessibility does not directly impact educational quality (β = 0.002, p = 0.955), thus not supporting H1. However, ICT accessibility significantly influences student engagement (β = 0.487, p = 0.000), and student engagement has a strong positive effect on educational quality (β = 0.500, p = 0.000), supporting H2 and H3. Importantly, mediation analysis confirmed that student engagement significantly mediates the relationship between ICT accessibility and educational quality (β = 0.244, p = 0.000), supporting H4. Effect size (f²) results indicated moderate impacts from ICT accessibility on student engagement (f² = 0.304) and from student engagement on educational quality (f² = 0.255), whereas ICT accessibility had no direct effect on quality education (f² = 0.000). Predictive relevance (Q²) values of 0.173 (quality education) and 0.145 (student engagement) confirmed the model’s robustness. The findings underscore the importance of fostering student engagement to maximize the educational benefits of ICT integration in Cambodian higher education.